Short animated film project Beauty and The Feast-- A study of non-stereotypical gender portrayal of a typically feminine role / Arina Izyan Ramli - Ramli, Arina Izyan (Faculty of Film, Theatre and Animation, 2014)
Many studies have been done to analyze gender representation in Disney films. In Malaysia, there have been significantly less gender-related studies focused on local animation. This study was carried out to investigate the gender roles and representation of female characters in Malaysian animated works. The findings from this analysis was used as support for the production of my short animated film project entitled Beauty and the Feast, in which I explored less stereotypical portrayals of a female character. A coded content analysis was carried out on several episodes taken from two Malaysian television series (Upin & Ipin, and BoBoiBoy), taking into account their current popularity among the target audience. The characters from these animations were investigated according to several stereotypical gender characteristics. Results suggest that both series portrays some degree of stereotypical representations of the female gender. In BoBoiBoy, though the female characters Yaya and Ying break away from some stereotypes by actively taking part in protecting the world from aliens, they still portray several stereotypical traits, such as being timid, and preferring not to fight. Although the characters in these series have portrayed non-stereotypical behavior at times, traditional ideals of femininity are still present in Malaysian animation. These findings enabled me to portray a female character that deviates from several gender stereotypes that are common in the animations studied. This research will contribute to the local literature on the issue of gender representation, and encourage more discussion regarding gender stereotypes in Malaysian media.